ANALISIS FAKTOR PENYEBAB KESULITAN MEMBACA PERMULAAN PESERTA DIDIK KELAS I PADA PEMBELAJARAN BAHASA INDONESIA - Nurul Hikmah Kartini; Masitoh Masitoh; M. Jailani (Jurnal Holistika, 2023)
This study aims to describe what are the factors that cause reading difficulties in the beginning of grade I students in Indonesian Language Learning at Public Alementary School 8 Pahandut Palangka Raya. This study uses a descriptive research method, a qualitative approach. The subjects or information in this study were 3 students in class I, class I teachers, class president of Public Alementary School 8 Pahandut Palangka Raya and parents of class I students. Data collection techniques in this study were observation, interviews and documentation. Based on the results of the study, it was found that students had difficulty in reading the beginning of Indonesian language learning, namely (1) internal factors (2) external factors, although not all students had difficulty in beginning reading. It is hoped that with this research, teachers should be able to train students in reading.